Myocardial uptake and clearance of thallium-201 in normal subjects: Comparison of dipyridamole-induced hyperemia with exercise stress - Ruddy, Terrence D.; Gill, John B.; Finkelstein, Dianne M.; William Strauss, H.; McKusick, Kenneth A.; Okada, Robert D.; Boucher, Charles A. (Journal of the American College of Cardiology, 1987)
Thallium-201 uptake and clearance after dipyridamole infusion may differ from that after exercise stress because the hemodynamic effects of these two interventions are different. In this study of normal volunteers, thallium kinetics after dipyridamole (n = 13) were determined from three serial image sets (early, intermediate and delayed) and from serial blood samples and compared with thallium kinetics after exercise (n = 15). Absolute myocardial thallium uptake was greater after dipyridamole compared with exercise (p < 0.0001), although the relative myocardial distribution was similar. The myocardial clearance (%/h) of thallium was slower after dipyridamole than it was after exercise. Comparing dipyridamole and exercise, the differences in clearance were large from the early to the intermediate image (anterior, −11 ± 17 versus 24 ± 5, p = 0.0005; 50° left anterior oblique, − 7 ± 11 versus 15 ± 8, p = 0.004; 70° left anterior oblique, 3 ± 9 versus 21 ± 6, p = 0.001). In contrast, the differences in clearance were small from the intermediate to the delayed image (anterior, 15 ± 4 versus 20 ± 2, p = 0.025; 50° left anterior oblique, 15 ± 4 versus 19 ± 3, p = 0.13; 70° left anterior oblique, 15 ± 3 versus 18 ± 2, p = 0.047). Thallium uptake and clearance in the liver, splanchnic region and spleen were greater after dipyridamole (p < 0.001). Blood thallium levels were greater after dipyridamole (p < 0.05) and cleared more slowly (p = 0.07). Thus, myocardial thallium-201 uptake and clearance after dipyridamole infusion differ from thallium kinetics after exercise. This difference is, in part, related to associated differences in extracardiac and blood kinetics. Diagnostic criteria for the detection of abnormal thallium-201 clearance must be specific for the type of intervention.